PENGELOLAAN ARSIP INAKTIF PADA DINAS PERIKANAN DAN PANGAN KOTA PADANG - Novitri, Aditia; Sari, Shinta Nofita (UIN Imam Bonjol Padang, 2025)
This study aims to describe and analyze the management of inactive archives at the Padang City Fisheries and Food Service. Inactive archives are archives that are rarely used but still have administrative, legal, and financial use value, so they must be stored systematically. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results showed that the management of inactive archives in the agency has not run optimally. The problems found include the absence of standard operating procedures (SOPs), low competence of human resources, limited storage facilities and infrastructure, and the absence of a digitalbased archival information system. In addition, the archive classification process has not yet referred to the Office Manuscript and the selection of inactive archives is not carried out based on the analysis of the use value of the archives. The organization of archives is also not systematic and not in accordance with ideal archival principles. Therefore, strategic efforts are needed in the form of drafting internal policies, training human resources, procuring supporting facilities, and implementing information technology to support professional and accountable archive management according to national standards.